Data created by the internet of things: the new gold without ownership? - Thomas J. Farkas (La Propiedad Inmaterial, 2017)
Data has become an asset with a big financial impact. With the extensive use of the Internet which “never forgets”, society has become more transparent than ever. Society also creates more data than ever. The increase of data creation is further catalysed by new technologies and connected devices; it is often referred to as the “internet of things” or “IoT-devices”. But who owns the date created by these new devices? This article aims to give a brief overview of possible rules governing data ownership. Also, it stresses the question whether or not the current legal framework sufficiently protects said data or if a new law should be implemented.